The Reality of Takaful Insurance in Algeria: A Study of the Experience of the Salama Insurance Company in Algeria - Ahmed, Boudeghdegh (Finance and Business Economies Review, 2022)
The aim of this study is to present the reality of takaful insurance in Algeria, as it was addressed through Salama Insurance Company, which is considered the only one in Algeria so far. We have concluded that the application of Takaful insurance in Algeria faces many obstacles, the basis of which is the legal challenge that constitutes the biggest obstacle to the development of this industry, as well as the traditional legal environment that often does not comply with Islamic Sharia regulations, as well as the weak efforts of the state in regulating the Takaful insurance industry, The failure to enact laws in line with its requirements, the weak technical and legal training of the human factor, the weak culture and insurance awareness of the Algerian public, all of which stand in the way of the development and growth of Takaful insurance